1999
DOI: 10.1159/000014166
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Genes of Arginine-Synthesizing Enzymes in the Rat Kidney during Development

Abstract: The expression of two genes, coding for argininosuccinate synthetase (ASS) and argininosuccinate lyase (ASL), enzymes which synthesize arginine, was studied by Northern analysis in various tissues of fetal rats. The highest expression of both genes was seen in the small intestine, liver and kidney of the fetus. The developmental expression was observed in the kidney where both mRNA levels remained low during the fetal period and they increased concomitantly in both kidney and liver throughout the perinatal lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
1
9
0
1
Order By: Relevance
“… Tissue distribution of ASS mRNA during adult and fetal periods in rats. Total RNA (25 µg per lane) was prepared from various tissues of adult (A) and 19.5‐day‐old fetuses (B) rats, and analysed by Northern blot (see [110] for experimental protocol). Hybridizations were performed successively with the ASS cDNA and the 18S rRNA probe as an internal standard.…”
Section: Ass a Ubiquitous Enzymementioning
confidence: 99%
See 2 more Smart Citations
“… Tissue distribution of ASS mRNA during adult and fetal periods in rats. Total RNA (25 µg per lane) was prepared from various tissues of adult (A) and 19.5‐day‐old fetuses (B) rats, and analysed by Northern blot (see [110] for experimental protocol). Hybridizations were performed successively with the ASS cDNA and the 18S rRNA probe as an internal standard.…”
Section: Ass a Ubiquitous Enzymementioning
confidence: 99%
“…Levels of mRNA (open circles) and enzyme activity (black circles) are shown. Data are from [60,110]. Adult values were taken as reference (100%); ASS activity in adult was 110.9 ± 11.7 U·g −1 liver, n = 7.…”
Section: Ass a Key Step In Urea Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…l-Cit is endogenously synthesized from l-glutamine in the intestines and released to the venous blood, 20 filtered in the glomeruli, and subsequently taken up by the proximal tubule. Proximal tubular cells express both argininosuccinate synthase and argininosuccinate lyase 27,28 and can, therefore, convert l-Cit to lArg. 21 The intestinal-renal axis of de novo synthesis of l-Arg from l-glutamine has been demonstrated using radiolabeled l-glutamine.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the expression of ASS and ASL genes based on the measurement of their transcripts, proteins, and enzyme activities has been reported during development of rat [6,7] and mouse [8] kidneys as well as in adult rat [9][10][11] and mouse [12] kidneys. Physiological studies clearly demonstrated the renal synthesis of L-arginine by quantitating arterial and renal venous concentrations of L-citrulline and L-arginine.…”
Section: Introductionmentioning
confidence: 99%